Inverse Nodal Problem for the Differential Operator with a Singularity at Zero - Yilmaz, Emrah; Koyunbakan, Hikmet; Ic, Unal (Tech Science Press, 2013)
In this study, some results are given about Sturm-Liouville operator having a singularity at zero. For this problem, asymptotic form of nodal data and a reconstruction formula for the potential function are given. In addition, a numerical example is established and illustrated the results in some tables and graphics.
Keywords: Inverse Nodal Problem; Reconstruction Formula; Nodal Points